Effect of coating on the color and surface hardness of the surface of dental ceramics - Esra Kul; Funda Bayindir; Pinar Gül; Ruhi Yesildal; Khamirul Amin Matori (Wolters Kluwer Medknow Publications, 2021)
Background: The aim of this study was to investigate whether boron nitride (BN) and BN-chromium (BN-Cr) coatings applied with the sputtering method would change the characteristics of hardness and discoloration of the ceramic veneer surface. Materials and Methods: In this experimental study, thirty disc-shaped cores (10 mm in diameter and 0.8 mm in thickness) were prepared. Three different ceramic systems, IPS Empress (E) (Ivoclar Vivadent, Schaan, Liechntenstein), IPS e.max Press (EP) (Ivoclar Vivadent, Schaan, Liechntenstein), and Turkom Cera (T) (Turcom-Ceramic SDN-BHD, Kuala Lumpur, Malaysia), were tested, each with n = 10. The specimens were divided into two subgroups (n = 5) according to the coating on the veneering ceramic: BN or BN-Cr. The Vickers hardness and color differences (ΔE) values were measured before and after coating. Surface analysis was performed with X-ray diffraction, X-ray photoelectron spectroscopy, and scanning electron microscopic. The Wilcoxon signed-rank test was performed to compare hardness values. The Kruskal-Wallis test was performed to compare ΔE values among all groups. The post hoc tests was used after Kruskal-Wallis, with level of statistical significance set at P ≤ 0.05. Results: BN-Cr coating statistically significantly increased the hardness of all types of ceramics (P < 0.05). BN coating did not change the hardness statistically significantly (P > 0.05). The mean ΔE values indicated clinically noticeable (over the limit of 3.7) color change in all groups except for the EP-BN and T-BN groups. Conclusion: Although BN-Cr coating in this thickness had a negative effect on color, it increased the hardness of the ceramics and could be useful in the palatal region.